The Chaco Mission Frontier : The Guaycuruan Experience - Saeger, James Schofield (Book collections on Project MUSE., 2000)
"By showing that the Guaycuruans were not as restricted in missions as has been assumed, Saeger demonstrates that there is a distinct difference between the establishment of missions and conquest. The Chaco Mission Frontier helps redefine mission studies by correcting over-generalization about their role in Latin America."--Jacket.